2023
DOI: 10.3389/fimmu.2023.1096323
|View full text |Cite
|
Sign up to set email alerts
|

Virus induced dysbiosis promotes type 1 diabetes onset

Abstract: Autoimmune disorders are complex diseases of unclear etiology, although evidence suggests that the convergence of genetic susceptibility and environmental factors are critical. In type 1 diabetes (T1D), enterovirus infection and disruption of the intestinal microbiota are two environmental factors that have been independently associated with T1D onset in both humans and animal models. However, the possible interaction between viral infection and the intestinal microbiota remains unknown. Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The experimental findings reported here are consistent with much of the previously published literature concerning T1DM etiology and pathogenesis. While a variety of viruses and bacteria have been associated with T1DM onset (reviewed in [76]), enteroviruses, and in particular COX, have been the ones most consistently identified through methods ranging from direct virus isolation to antibody cross-reactivity to microbiome studies [12][13][14][15][16][17][18][19][19][20][21][22][23][48][49][50][51][52][53][54][55][56][76][77][78][79][80][81]. Our results also make a strong case of a role for enteroviruses in T1DM etiology but suggest that the main target of enterovirus antibodies is not INS (as most previous research has attempted to demonstrate) but rather INSR, a T1DM target other investigators have previously reported [4][5][6][7][8][9]54,[82][83][84][85][86].…”
Section: Relationship Of the Experimental Findings To Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental findings reported here are consistent with much of the previously published literature concerning T1DM etiology and pathogenesis. While a variety of viruses and bacteria have been associated with T1DM onset (reviewed in [76]), enteroviruses, and in particular COX, have been the ones most consistently identified through methods ranging from direct virus isolation to antibody cross-reactivity to microbiome studies [12][13][14][15][16][17][18][19][19][20][21][22][23][48][49][50][51][52][53][54][55][56][76][77][78][79][80][81]. Our results also make a strong case of a role for enteroviruses in T1DM etiology but suggest that the main target of enterovirus antibodies is not INS (as most previous research has attempted to demonstrate) but rather INSR, a T1DM target other investigators have previously reported [4][5][6][7][8][9]54,[82][83][84][85][86].…”
Section: Relationship Of the Experimental Findings To Previous Resultsmentioning
confidence: 99%
“…COX antibodies do not appear to be cross-reactive with INS, nor are INS antibodies cross-reactive with COX [54]. Moreover, although evidence of COX infections appears in temporal relationships with subsequent T1DM diagnosis [50,55,56], at least one live enterovirus vaccine-oral polio-is not associated with any increased risk of T1DM, even among genetically high-risk individuals [57,58]. However, COX infections have been linked to the development of INS receptor antibodies [59].…”
Section: Introductionmentioning
confidence: 99%
“…A link between NEC and CVs was first observed in the 1970s, with fatal cases related to CVB2 and CVB3 ( Johnson et al, 1977 ; Behrman, 1976 ). Finally, it's important to highlight that many virus infections, particularly those associated with the gut, can result in dysbiosis and disruption of intestinal homeostasis prior to gastrointestinal manifestations onset ( Harper et al, 2021 ; Morse et al, 2023 ). As a result, the dysbiosis caused by viral infection can favor an increase in potentially pathogenic bacteria, while decreasing the organisms considered to be beneficial ( Harper et al, 2021 ).…”
Section: Cv-associated Infectionsmentioning
confidence: 99%
“…Individuals with T1D often have features of a dysregulated microbiome, possibly linked to changes in gut permeability 33 or viral infection 34 , 35 . Interestingly, high-risk HLA haplotypes (such as HLA class II DR3/DR4-DQ2/8) were associated with a potential loss of tolerance and antibody development to host commensal microorganisms 36 .…”
Section: Enviromental Factors Implicated In T1dmentioning
confidence: 99%
“…Their dysfunction and loss of microbiome diversity can lead to loss of tolerance to commensal bacteria and allow the outgrowth of inflammation-inducing species that may affect local tolerance mechanisms, enhance the function of autoreactive cells or even activate immune cells that have cross-reactivity between commensal bacteria and autoantigens 36 . In addition, metabolic products of the microbiome, such as short-chain fatty acids (SCFA), may affect systemic immune regulation, including via direct effects on mucosal-associated invariant T (MAIT) cells 34 , 37 , 38 , 229 , 230 . Antibodies to commensal microbiota have been identified in individuals at risk for T1D, and in non-obese diabetic mice, cross-reactive antigens that are recognized by CD8 + T cells were found (not shown) 24 , 25 , 117 .…”
Section: Road To Development Of Therapies For the Treatment And Preve...mentioning
confidence: 99%